Arithmetic and Huffman Coding using Quasi-Cyclic Low Density Parity Check Techniques with F-OFDMA for 5G System - Idris, Azlina; Aini Amran, Nurul; Syarhan Idris, Mohd; Taib, Idris; Kassim, Murizah; Seroja Sarnin, Suzi; Norsyafizan W Muhammad, Wan; Ya’acob, Norsuzila (International Journal of Engineering and Technology, 2018)
The rising demand of the future 5th generation (5G) wireless systems has led to the development of wireless communication technologies that can provide higher user capacity. Therefore, filtered orthogonal frequency division multiple access (F-OFDMA) was introduced to accommodate large number of users. F-OFDMA has the advantage over OFDM since it is capable of overcoming the high side lobes and increasing the spectrum utilization by eliminating the out-of-band emission which can degrade the systemâ€™s performance. In this paper, a joint method between two block coding techniques (Arithmetic coding (AC) and Huffman Coding (HC)) with an error correcting code (Quasi-Cyclic Low Density Parity Check (QC-LDPC))was proposed. AC-QC-LDPC and HC-QC-LDPC schemes were compared in terms of BER performance. Based on the simulation results, AC-QC-LDPC technique has been proven to give the 44.75% BER improvement to the F-OFDMA system which outperforms the HC-QC-LDPC technique. It is clear from the results that Arithmetic coding always give better BER improvements compared to Huffman coding with QC-LDPC.Â